Pemanfaatan Artificial Intelligence untuk Peningkatan Motivasi dan Produktivitas Belajar di SMA YA BAKII Kesugihan - Abdul Azis; Safiq Rosad; Anton Yudhana; Sunardi (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
The use of Artificial Intelligence (AI) technology in education provides innovative solutions to challenges faced in the learning process, such as limited teaching resources, variations in student learning styles, and the need to improve motivation and learning productivity. Ya BAKII Kesugihan Senior High School (SMAYA), a boarding school-based in Kesugihan District, Cilacap Regency, Central Java Province, integrates general and religious education in a comprehensive manner. However, teachers at SMAYA still have limited mastery of AI (Chatgpt, Gamma, Wordwall, and Deppl), technology, while digital technology continues to develop rapidly. Therefore, specialized training on the appropriate use of AI technology in alignment with religious values and boarding school culture is necessary. This training aims to enable teachers at SMAYA to understand and master AI technology, implement it in more personalized and adaptive learning processes, and enhance students' motivation and productivity. As a result, it is hoped that the quality of education at SMAYA will improve, bridge the digital divide, and promote competitive education in the globalized era.